Hope, Symptoms, and Palliative Care: Do Symptoms Influence Hope?. (April 2017) - Davis, Mellar P.; Lagman, Ruth; Parala, Armida; Patel, Chirag; Sanford, Tanya; Fielding, Flannery; Brumbaugh, Anita; Gross, James; Rao, Archana; Majeed, Sumreen; Shinde, Shivani; Rybicki, Lisa A.
Background: Hope is important to patients with cancer. Identifying factors that influence hope is important. Anxiety, depression, fatigue, and pain are reported to impair hope. The objective of this study was to determine whether age, gender, marital status, duration of cancer, symptoms, or symptom burden measured by the sum of severity scores on the Edmonton Symptom Assessment Scale (ESAS) correlated with hope measured by the Herth Hope Index (HHI). Methods: Patients with advanced cancer in a palliative care unit participated. Demographics including age, gender, marital status, cancer site, and duration of cancer were collected. Individuals completed the ESAS and HHI. Spearman correlation and linear regression were used to assess associations adjusting for gender (male vs female), age (< 65 vs ≥ 65 years), marital status (married or living with a partner vs other), and duration of cancer (≤ 12 vs > 12 months). Results: One hundred and ninety-seven were participated in the study, of which 55% were female with a mean age of 61 years (standard deviation 11). Hope was not associated with gender, age, marital status, or duration of cancer. In univariable analysis, hope inversely correlated with ESAS score (−0.28), lack of appetite (−0.22), shortness of breath (−0.17), depression (−0.39), anxiety (−0.32), and lack of well-being (−0.33); only depression was clinically relevant. In multivariable analysis, total symptom burden weakly correlated with hope; only depression remained clinically significant. Discussion: This study found correlation between symptom burden and hope was not clinically relevant but was so for depression. Conclusion: Among 9 ESAS symptoms, only depression had a clinically relevant correlation with hope.